2017
DOI: 10.24264/lfj.17.3.7
|View full text |Cite
|
Sign up to set email alerts
|

Footwear Protection against Fungi Using Thyme Essential Oil

Abstract: ABSTRACT. Many natural antimicrobial agents have been identified over the last decades, such as essential oils, which have a proven effect against bacteria and fungi found on feet. This paper investigates antifungal activity of thyme essential oil against Trichophyton interdigitale on sheepskins for footwear lining. Thyme essential oil showed the best antifungal activity on sheepskins for footwear lining. Thyme oil offers a much safer alternative to toxic biocides. The results of this study may have potential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
1
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 10 publications
2
5
0
Order By: Relevance
“…The chemical composition of the essential oils consists of a mixture of compounds, in different percentages, which together give the specific bioactive properties. Thyme and oregano essential oils used were analysed with Agilent 6890 N GC-MS highlighting the main constituent compounds: carvacrol 57.4%, α-terpinene 32.4%, o-cymol 3.9%, for thyme essential oil [30] and thymol 64.4%, carvacrol 27.6%, limonene 3%, for oregano essential oil [31]. These compounds compositions are in agreement with those found in literature [32].…”
Section: Essential Oils (Eos)supporting
confidence: 86%
“…The chemical composition of the essential oils consists of a mixture of compounds, in different percentages, which together give the specific bioactive properties. Thyme and oregano essential oils used were analysed with Agilent 6890 N GC-MS highlighting the main constituent compounds: carvacrol 57.4%, α-terpinene 32.4%, o-cymol 3.9%, for thyme essential oil [30] and thymol 64.4%, carvacrol 27.6%, limonene 3%, for oregano essential oil [31]. These compounds compositions are in agreement with those found in literature [32].…”
Section: Essential Oils (Eos)supporting
confidence: 86%
“…Globosum and C. albicans. The strong properties of thyme oil were also confirmed in other research [12,13].…”
Section: Table 2 Grading Scale For Visible Antifungal Effectssupporting
confidence: 76%
“…The study of Chirila et al (2017) showed that Thymus vulgaris oil exhibited high antifungal activity against Candida albicans and Aspergillus niger. Thyme oil could be the best inhibitor of fungi due to the high thymol and carvacrol content [12].…”
Section: Table 2 Grading Scale For Visible Antifungal Effectsmentioning
confidence: 99%
“…Plants with bioactive properties are part of the important group of plants traditionally used to prevent and treat the development of fungi and bacteria [2,3]. Essential oils from plants are highly concentrated compositions in chemical compounds with important bioactivity, which have several properties: antiseptic, antibacterial, immunostimulant, regenerative, anticancer [4][5][6][7][8][9][10]. Essential oils are liquid, volatile, clear, or colored, soluble in lipids and organic solvents, having densities generally lower than water [11][12][13].…”
Section: Introductionmentioning
confidence: 99%